Implementation of School Committee Empowerment as Supporting Sector in Education at Juara Elementary Yogyakarta - Suryo Utomo , Raden Adji; Hidayati, Dian (Yayasan Lembaga Studi Makwa, 2025)
This study aims to analyze the implementation of school committee empowerment as a supporting sector for the education process at SD Juara in Yogyakarta City in 2021. The research was conducted to identify how the school committee contributes to the effectiveness of educational management and to evaluate the extent of its empowerment in various school aspects. The research subjects consisted of 11 respondents, including the principal, the committee chairperson, secretary, treasurer, public relations officer, representatives of grade 1 and grade 6 school committee members, as well as school representatives in the fields of curriculum, student affairs, finance, and facilities and infrastructure. The study applied a qualitative descriptive method, with data collected through interviews, documentation, and observation. The data analysis was carried out through the stages of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the school committee was effectively empowered in supporting the curriculum, finance, human resources, and facilities and infrastructure management. However, the role of the school committee in the area of student affairs was found to be less optimal, showing limited contribution in this aspect. This reveals that while the committee has made significant contributions in some areas, there remains a need to strengthen its involvement in supporting student development more comprehensively. The implications of this study highlight the importance of reinforcing the role of school committees in student affairs, so that empowerment can be implemented in a balanced way across all aspects of education at SD Juara.